Microstructure, magnetic and optical properties of Nb3+ and Y3+ ions co-substituted Sr hexaferrites. Issue 4 (March 2020) - Güner, S.; Almessiere, M.A.; Slimani, Y.; Baykal, A.; Ercan, I.
Abstract: Series of SrNbx Yx Fe12-2x O19 (0.00 ≤ x ≤ 0.05) hexaferrites (HFs) were fabricated via citrate sol-gel approach. Structural and magneto-optical properties of ensembles were investigated in detail. The structural and morphological analyses revealed the formation of M-type Sr hexaferrite nanoparticles. Diffuse reflectance data were registered to estimate the direct optical energy band gaps ( E g ) in a range of 1.77 eV-1.87 eV. Room temperature (RT, 300 K) and low temperature (10 K) magnetic hysteresis curves were recorded by enforcing applied dc magnetic field up to ±70 kOe. Magnetic parameters were significantly tuned due to coordination of Nb 3+ and Y 3+ rare earth ions. Specified magnetic data reveal the strong ferromagnetic characteristics of pristine SrFe12 O19 and co-doped HFs with Nb 3+ and Y 3+ ions at both temperatures. RT squareness ratio (SQR) has an exception only for pristine sample as 0.506, which is in the margin of theoretical limit assigning the single-domain nature with uniaxial anisotropy. However, all co-doped samples have SQR = 0.288–0.485 values that are smaller than theoretical limit of 0.50, implying multi-domain nature at RT and at 10 K. Co-doped ions cause lowering in super-exchange interactions between different sites and resulting the decrements of intrinsic magneto-crystalline anisotropy and coercivity fields. The specified magnetic characteristics make our fabricated SrNbx Yx Fe12-2x O19 (0.00 ≤ x ≤ 0.05) HFs good candidates as permanent magnets applications and high-density recording media.